(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The aim of this article was to present crip dramaturgies as an operative and political logic to create dance. Since the years 1990, the main researches of the area, had already recognized the importance of the body and the movement, beyond the verbal language and theatrical texts. But what is established after 2000 with the crip theories is the emphasis in the failure, in the decentralization of human life and in the defunctionalization of the body-organism as a power of creation open to other bodies (animate and inanimate). Artists from diverse cultural contexts have created their dance dramaturgies as devices to highlight singularities, include other lives, and activate non-anthropocentric strategies of creation. In this sense, we highlight the research of the Korean Jeong Geumhyung, the Chilean Manuela Infante and the Brazilian Eduardo Fukushima.